Renal Rangers: Pendampingan Pasien Gagal Ginjal Kronik dengan Pendekatan Dukungan Keluarga sebagai Inovasi untuk Meningkatkan Efikasi Diri Pasien - Khoiroh Yeroh (Jurnal Studi Inovasi, 2022)
Chronic kidney disease is a disease suffered globally with an increasing prevalence. This can occur due to the lack of family knowledge in motivating patient to take proper fluid intake and diet. So that nurse efforts are needed ini increasing the collaborative role of family to increase self-efficacy in patient. This study aims to find out how nurses improve the self-efficacy of chronic kidney disease throught a family support approach. This research uses the literature study method, which coome from various type of literature. The relevant references are sorted and analyzed descriptively and argumentatively and make ac conclusions according to research objectives. Based on literature review, samily support from both family members anda relatives can play a role in increasing patient cofidence in undergoing treatment. This support can be motivation or information. Education and information related to chronic kidney disease can be obtained through the RenalRanger, which is a teamof companions from the community. In addition to education, there is a home blood pressure monitoring training program for patients. Education was given using booklet media and participants were given a diet monitoring sheet. The sheet needs to be filled in independently with family assistance, by writing down fluid intake and output on a regular basis. As an evaluation of the patient achievement during the mentoring process. In the early stage, the patient will have a discussion with the facilitator regarding chronic kidney disease. Furthermore, the provision of knowledge to change the lifestyle so that patient self efficacy can improve. The next sage the patient is askes to share information with family about the material that has been studied. This stage aims to increase the ablyty to maintain health and improve patient self-esteem.